* Your assessment is very important for improving the work of artificial intelligence, which forms the content of this project

Survey

* Your assessment is very important for improving the work of artificial intelligence, which forms the content of this project

Document related concepts

Line (geometry) wikipedia, lookup

Elementary mathematics wikipedia, lookup

Recurrence relation wikipedia, lookup

Fundamental theorem of algebra wikipedia, lookup

Factorization wikipedia, lookup

Elementary algebra wikipedia, lookup

History of algebra wikipedia, lookup

Transcript

Quadratic Equations P.7 Definition of a Quadratic Equation • A quadratic equation in x is an equation that can be written in the standard form • ax2 + bx + c = 0 • where a, b, and c are real numbers with a not equal to 0. A quadratic equation in x is also called a second-degree polynomial equation in x. The Zero-Product Principle If the product of two algebraic expressions is zero, then at least one of the factors is equal to zero. If AB = 0, then A = 0 or B = 0. Solving a Quadratic Equation by Factoring 1. If necessary, rewrite the equation in the form ax2 + bx + c = 0, moving all terms to one side, thereby obtaining zero on the other side. 2. Factor. 3. Apply the zero-product principle, setting each factor equal to zero. 4. Solve the equations in step 3. 5. Check the solutions in the original equation. Text Example • Solve 2x2 + 7x = 4 by factoring and then using the zero-product principle. Step 1 Move all terms to one side and obtain zero on the other side. Subtract 4 from both sides and write the equation in standard form. 2x2 + 7x - 4 = 4 - 4 2x2 + 7x - 4 = 0 Step 2 Factor. 2x2 + 7x - 4 = 0 (2x - 1)(x + 4) = 0 Solution cont. • Solve 2x2 + 7x = 4 by factoring and then using the zero-product principle. Steps 3 and 4 Set each factor equal to zero and solve each resulting equation. 2x-1=0 or x + 4 = 0 2x=1 x = -4 x = 1/2 Steps 5 check your solution Example (2x + -3)(2x + 1) = 5 4x2 - 4x - 3 = 5 4x2 - 4x - 8 = 0 4(x2-x-2)=0 4(x - 2)*(x + 1) = 0 x - 2 = 0, and x + 1 = 0 So x = 2, or -1 The Square Root Method If u is an algebraic expression and d is a positive real number, then u2 = d has exactly two solutions. If u2 = d, then u = d or u = -d Equivalently, If u2 = d then u = d Completing the Square If x2 + bx is a binomial then by adding (b/2) 2, which is the square of half the coefficient of x, a perfect square trinomial will result. That is, x2 + bx + (b/2)2 = (x + b/2)2 Text Example What term should be added to the binomial x2 + 8x so that it becomes a perfect square trinomial? Then write and factor the trinomial. The term that should be added is the square of half the coefficient of x. The coefficient of x is 8. Thus, (8/2)2 = 42. A perfect square trinomial is the result. x2 + 8x + 42 = x2 + 8x + 16 = (x + 4)2 x2 + 6x = 7 B divided by 2, squared x2 + 6x + 9 = 7 + 9 x + 3 2 = 16 x + 3 = 4 x = 4 - 3 x = 1, or - 7 Don’t forget to add to both sides Quadratic Formula - b b - 4ac x= 2a 2 x 2 - 8x + 5 = 0 x 2 - 8x + 5 = 0 - (-8) ( -8) 2 - 4(1)(5) x= 2(1) 8 64 - 20 x= 2 8 44 x= 2 8 2 11 x= 2 2( 4 11) x= 2 x = 4 11 The Discriminant and the Kinds of Solutions to ax2 + bx +c = 0 Discriminant b2 – 4ac Kinds of solutions to ax2 + bx + c = 0 b2 – 4ac > 0 Two unequal real solutions Graph of y = ax2 + bx + c Two x-intercepts b2 – 4ac = 0 One real solution (a repeated solution) One x-intercept b2 – 4ac < 0 No real solution; two complex imaginary solutions No x-intercepts